Enhancing Cognitive and Communication Skills in Learning Chemistry through Case-Based Learning Integrated with Question and Answer and Whole-Class Discussion Methods - Asmiyunda, Asmiyunda; Asrial, Asrial; Sanova, Aulia; Miharti, Isra (FKIP Universitas Lampung, 2025)
Abstract: The objective of this study is to assess the efficacy of a Case-Based Learning (CBL) model integrated with a question-and-answer method and class discussion in enhancing students' cognitive and communication skills. The research employed a one-group pretest-posttest experimental design. The subjects of the study were third-semester students enrolled in an inorganic chemistry 1. Intially, students were assessed through a pretest designed to measure their cognitive and communication skills. After implementation of the CBL model, followed by question-and-answer sessions and class discussion, a posttest was conducted to evaluate improvements in these skills. The results demonstrated significant enhancement in students' cognitive and communication abilities. The CBL model encouraged students actively analyze authentic cases and articulate logical solutions, thereby strengthening their critical thinking and oral communication skills. Based on these findings, it can be concluded that the model is medium effective in enhancing the quality of learning, particularly in developing students' cognitive and communication skills in inorganic chemistry courses. Keywords: cognitive, communication, case-based learning model.